Strategi Pengembangan Hutan Rakyat Berbasis Tanaman Karet (Hevea Brasiliensis) Di Kabupaten Tebo - Rina Yuli Rahmawati; Heriberta .; Zamzami .; Siti Hodijah; Nurhayani . (JOURNAL OF SHARIA ECONOMICS, 2025)
Rubber-based community forest management in Tebo Regency offers opportunities to improve farmer welfare while maintaining environmental function and resource sustainability. This article analyzes the existing conditions, obstacles, and strategies for rubber-based community forest development, and recommends a framework for strengthening this sector in Tebo Regency.The study reveals that smallholder rubber productivity is low, many plantations are aging, the quality of processed materials is poor, and land conversion to other commodities (e.g., oil palm) poses a threat to sustainability. Therefore, integrated technological, institutional, market, and policy interventions are needed.